Examwiz: a development and implementation of an android based examination - R., Rifin; Fang, T. E.; A. F. Z., Abidin; Asrul, Adam; M. A., Majid; A., Zainuddin; S. H., Mohammad; M. H., Harun; Z. I., Rizman (University of El Oued (Algeria), 2018)
The development pace of smartphone has been phenomenal in the past decade. Although the information technology and mobile technology have been developing rapidly, the examinations in a lot of schools, institutions and universities are still very conventional. The conventional exam method has brought more problems to the educational institutions in terms of building exam questions, marking and waste of papers. To overcome and solve the issues which the institutions are facing, the “ExamWiz” mobile app is designed to ease the painful of exam process.The exam mobile app allows students to attempt the exam using their own smartphone, to check the past results and to view their academic records. The mobile app is integrated with server application with a set of web services. It is the exam server that allows instructor to create questions, setup exam and view exam results.